Agile Development & Business Goals: The Six Week Solution - Holtsnider, Bill (Elsevier, 2011)
Agile Development and Business Goals describes a unique, state-of-the-art methodology that aligns the critical but often "silo-ed" software development process with core company goals. Eschewing long-winded "agile philosophy" in favor of a formally prioritized process, this book serves as a distilled learning guide for managing technical resources in a manner that directly boosts your bottom line. Build the teams, define the roles, acquire the tools, and deliver your world-class software on time and on budget.